Experimental Analysis of an Instrumented Charpy Impact Using Signal Processing Approach - Ali, Mohd Basri (Scientific.Net Materials Science and Engineering, Switzerland, 2011)
The dynamic responses of the standard charpy impact machine are experimentally studied using the relevant data acquisition system in order to obtain the impact response. For this reason, strain gauges were connected to the data acquisition set and it was then attached to the charpy striker for the signal collection. Aluminium 6061 and low carbon steel 1050 were used for extracting strain responses on the striker during the testing. In this work, the power spectrum density (PSD) approach was then used for the energy based observation and a signal was converted from the time domain to the frequency domain using the fast Fourier transform (FFT) method. Comparison between experimental findings with related parameters such as of different materials, strain signals pattern, I-kaz, were finally correlated and discussed. It was found that the modulus of elasticity were proportional to the energy absorbed, strain signals amplitude and PSD. Finally, it is suggested that the properties of materials and the impact signals pattern is suitable to be analysed using the signal processing approach.